INCOME ANALYSIS OF DEWA CARAMBOLA FARMING IN SAWANGAN SUBDISTRICT, DEPOK CITY, WEST JAVA - Lola Rahmadona; Febiola Devitasari (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
In 2009 dewa carambola was inaugurated as an icon of Depok City. This is because Depok City contributes quite a lot of carambola production in West Java Province. Sawangan sub-district was chosen as the research location because it is one of the centers for carambola production in Depok City. The occurrence of land-use change, the price of production inputs is increasingly high, and PDO (Plant Disturbing Organisms) are problems in the farming activities of the dewa carambola in Sawangan District. This study aimed to determine carambola farming characteristics and income analysis in the Sawangan District. Respondents were determined purposively with 30 farmers using the Slovin formula. In this study, the characteristics of the farm are described descriptively, and the analysis of farm income uses the R/C ratio analysis. The analysis results show that the total cost per hectare per year of carambola farming in Sawangan District is IDR 29,147,430,444. The result is the sum of the cash costs of IDR 20,644,741,935 per hectare per year and the calculated costs of IDR 8,502,688,508 per hectare per year. The highest cash costs incurred were wages for non-family labor (TKLK) of IDR 7,288,709,677/ha/yr. Meanwhile, the highest calculated cost is the TKDK fee of 65.90%, or around IDR 5,668,548,387 per hectare per year. Meanwhile, the income for carambola farming in Sawangan sub-district for cash costs is IDR 13,125,677,419 per hectare and the value of income for total costs is IDR 4,622,988,911 per hectare. The analysis results of the R/C ratio of cash costs are 1.63 and the R/C ratio of total costs is 1.15. So it can be said that carambola farming in Sawangan District is efficient or feasible to cultivate.